A Case Study of Learning Difficulties Leading to Students’ Inactive Participation in Classroom Learning at Junior High School - Agustinus Meo; Wens Nagul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze learning difficulties that lead to low levels of student participation in classroom learning and to identify the factors influencing this condition. The research employed a qualitative approach with a case study design. The research subject was a junior high school student who exhibited passive learning behavior and limited participation in classroom activities. Data were collected through observations, in-depth interviews with the student, subject teachers, the homeroom teacher, and the guidance and counseling teacher, as well as supporting documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that low student learning participation is influenced by internal factors, such as lack of concentration and self-confidence, as well as external factors, including the learning environment and teaching methods. Continuous guidance and counseling services, supported by collaboration among subject teachers and the homeroom teacher, play a crucial role in facilitating positive changes in students’ learning behavior. This study is expected to provide practical contributions to the development of school guidance and counseling services in addressing students’ learning difficulties in a comprehensive manner.